The First World War - Cawood, Ian.; McKinnon-Bell, David (London ; New York : Routledge, 2001)
Examines the outbreak, events themselves and the aftermath of the Great War, and the political, social and economic effects on the European countries involved.
Book Cover; Title; Contents; Series preface; Acknowledgements; Introduction; The outbreak of war; Recruitment and propaganda; Total war economic mobilisation and the war economy; The women's war; The changing role of government; Protest and pacifism; The fall of the Russian and German governments; Victory and defeat; Notes; Bibliography; Index.
Includes bibliographical references (pages 165-168) and index.
Print version record.
eBooks on EBSCOhost
Keywords: World War, 1914-1918.; Guerre mondiale, 1914-1918.; HISTORY -- Military -- World War I; 1914-1918